Reaction Mechanisms and HCCI Combustion Processes of Mixtures of n-Heptane and the Butanols - Wang, Hu; DelVescovo, Dan; Zheng, Zunqing; Yao, Mingfa; Reitz, Rolf D. (Frontiers in Mechanical Engineering, 2015)
A reduced primary reference fuel (PRF)-Alcohol-Di-tert-butyl Peroxide (DTBP) mechanism with 108 species and 435 reactions, including sub-mechanisms of PRF, methanol, ethanol, DTBP and the four butanol isomers, is proposed for homogeneous charge compression ignition (HCCI) engine combustion simulations of butanol isomers/n-heptane mixtures. HCCI experiments fuelled with butanol isomer/n-heptane mixtures on two different engines are conducted for the validation of proposed mechanism. The mechanism has been validated against shock tube ignition delays, laminar flame speeds, species profiles in premixed flames and engine HCCI combustion data, and good agreements with experimental results are demonstrated under various validation conditions. It is found that although the reactivity of neat tert-butanol is the lowest, mixtures of tert-butanol/n-heptane exhibit the highest reactivity among the butanol isomer/n-heptane mixtures if the n-heptane blending ratio exceeds 20% (mole). Kinetic analysis shows that the highest C-H bond energy in the tert-butanol molecule is partially responsible for this phenomenon. It is also found that the reaction tC4H9OH+CH3O2 =tC4H9O+CH3O2H plays important role and eventually produces the OH radical to promote the ignition and combustion. The proposed mechanism is able to capture HCCI combustion processes of the butanol/n-heptane mixtures under different operating conditions. In addition, the trend that tert-butanol /n-heptane has the highest reactivity is also captured in HCCI combustion simulations. The results indicate that the current mechanism can be used for HCCI engine predictions of PRF and alcohol fuels.